Automatic smoke detection system with favoriot platform using internet of things (IoT) - Mohd Alif bin Suparman; Siat Ling Jong (Institute of Advanced Engineering and Science, 2019)
The available fire alarm system in the market unable to inform occupant that their house is on fire. The occupant remains unknown especially when they are away from their house. Most of the time, the house or building almost destroyed by fire when firefighter comes to the scene due to late inform to Fire and Rescue Department. To this aim, automatic smoke detection system using Internet of Things (IoT) is proposed. The proposed system not only able to monitor the smoke condition of a room but also able to alert user and Fire and Rescue Department when certain level of smoke is detected by a gas sensor via Favoriot platform. Arduino Uno is used in this work to control all the devices and WiFi shield acts as a medium to interconnect devices with the network so that the data from the smoke sensor can be read in the Favoriot platform. In this experiment, the condition of room is tested under several burning materials and the smoke levels are recorded. It is found that when the smoke level more than 100 ppm, it may cause to sore eyes, cough and hard breathing that can bring to death. Therefore, the best threshold level of the automatic smoke detection system is at 80 ppm. By using this system, the user able to take preliminary rescue action to save people and prevent fire breaks out.